2019
DOI: 10.1002/slct.201903065
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Biological Activity of a New Cobalt(III) Complex through Loading into a Nanocarrier, and the Characterization Thereof

Abstract: In an effort to use a polymer carrier for the maintenance of biological activity of metal complexes; in this report, a novel cobalt(III) complex, trans‐[Co(en)2(mtzt)2]NO3 (1) was prepared (en=ethylenediamine and Hmtzt=1‐methyl‐1‐H‐1,2,3,4‐tetrazol‐5‐thiol) and fully characterized. A biocompatible di‐block polymer, containing poly lactic‐co‐glycolic acid and poly ethylene glycol (PLGA‐PEG), was employed as the nanocarrier of complex 1 to achieve more efficacy and controlled drug release. Results illustrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Especially, those possessing an auxiliary ligand have been a subject of intensive research in recent years [2][3][4]. On the purpose of their interest structures, some of these hybrid compounds exhibit interesting applications which have been expanded to pharmacological and biological activities such as antimicrobial [5], anti-inflammatory [6]anticancer [7], antidiabetic, antimalaria [8], and antioxidant activities in addition to their catalytic properties in redox reactions [9], benzoate is used as an antimicrobial agent in edible coatings [10]. Also, sodium benzoate is used in cosmetic and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, those possessing an auxiliary ligand have been a subject of intensive research in recent years [2][3][4]. On the purpose of their interest structures, some of these hybrid compounds exhibit interesting applications which have been expanded to pharmacological and biological activities such as antimicrobial [5], anti-inflammatory [6]anticancer [7], antidiabetic, antimalaria [8], and antioxidant activities in addition to their catalytic properties in redox reactions [9], benzoate is used as an antimicrobial agent in edible coatings [10]. Also, sodium benzoate is used in cosmetic and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Abedi and coworkers investigated the biological activity of the new cobalt(III) complex ( Co1 ) in its free form. They encapsulated it into a nanocarrier composed of PLGA–PEG di-block copolymer [ 153 ]. They observed that Co1 -loaded PLGA–PEG NPs have pH-dependent release.…”
Section: Non-platinum-containing Metal Therapeutic Agents Loaded Into...mentioning
confidence: 99%
“…They observed that Co1 -loaded PLGA–PEG NPs have pH-dependent release. In addition, Co1 -loaded PLGA–PEG NPs presented enhanced antiproliferative activity toward Gram-positive and Gram-negative bacteria and against ovarian cancer cells (A2780) compared to the free complex [ 153 ].…”
Section: Non-platinum-containing Metal Therapeutic Agents Loaded Into...mentioning
confidence: 99%